Changes after a conventional vs. An alternative therapy program on physical, psychological, and injury-related parameters in male youth soccer players with patellar tendinopathy during return to competition - Niering, M.; Muehlbauer, T. (The Journal of Strength and Conditioning Research, 2023)
Changes after a conventional (CON) vs. alternative (ALT) therapy program on physical, psychological, and injury-related or pain-related parameters in soccer players with patellar tendinopathy (PT) during return to competition were examined. Thirty-four male youth soccer players (15-16 years) with PT were randomly assigned to a CON (n = 18) or ALT (n = 16) program. The ALT program consisted of 60 minutes of balance training, eccentric and isometric exercises, static stretching, and a dual-task progression. The CON program consisted of 30 minutes of eccentric and isometric exercises and static stretching. Both programs were conducted until painlessness was reported during full training load. Assessments of muscle power (drop jump, jump and reach), change of direction speed (CODS) (acyclic sprint), speed (tapping, 30-m linear sprint), endurance (Yo-Yo intermittent recovery test level-1), the Achievement Motives Scale Sport, and injury-related or pain-related correlates were performed immediately, 6 weeks, 16 weeks, and 20 weeks after the respective therapy program. Players in the ALT group required a shorter program duration (ALT: 47.1 ± 15.6 days, CON: 58.2 ± 24.6 days) and achieved the same (muscle power, speed, endurance) or greater (CODS) improvements in physical performances, the same enhancements in psychological measures (achievement motives), and better values for injury-related or pain-related correlates (injury incidence, pain-related training interruptions). Results indicate that both programs effectively improve relevant outcome parameters in players with PT. The ALT therapy is more time efficient than the CON therapy. Therapists should consider this multimodal training program for effective treatment of athletes to shorten their return to competition time and minimize the risk of secondary injuries.